Synthesis and evaluation of novel two-photon fluorescence probes for in vivo imaging of amylin aggregates in the pancreas. (November 2019) - Watanabe, Hiroyuki; Miki, Yusuke; Shimizu, Yoichi; Saji, Hideo; Ono, Masahiro
Abstract: The deposition of islet amyloid consisting of amylin aggregates is one of the hallmarks of type 2 diabetes mellitus (T2DM). Therefore, the amylin aggregate is regarded as an attractive target for diagnosis, treatment and elucidation of the pathogenic mechanism of T2DM. However, no fluorescence probe for in vivo imaging of amylin aggregates has been reported. In this study, we evaluated four fluorescent probes (DANIRs) including two novel compounds (DANIR-OH 2b and DANIR-OH 2c) for two-photon fluorescence imaging of amylin aggregates in the pancreas. All DANIRs showed binding affinity for amylin aggregates and clearly stained amylin aggregates in pancreatic sections of the islet amylin model mice and T2DM patients in in vitro . In an ex vivo fluorescence staining study, these probes also bound to amylin aggregates in the pancreas of the islet amylin model mice. Furthermore, in an in vivo two-photon fluorescence imaging study, we clearly imaged the amylin aggregates after injecting DANIRs via the tail vein of the islet amyloid model mice. The results suggest that DANIRs may be useful for two-photon fluorescence imaging of amylin aggregates in the living mouse pancreas. Graphical abstract: Image 1 Highlights: We evaluated four fluorescent probes (DANIRs) for two-photon fluorescence imaging of amylin aggregates in the pancreas. DANIRs showed binding affinity for amylin aggregates in in vitro. DANIRs clearly visualized amylin aggregates in the in vivo two-photon fluorescence imaging study. DANIRs are the first probes for in vivo imaging of amylin aggregates with two-photon microscopy.